SISTEM INFORMASI GEOGRAFIS DALAM PENCARIAN LOKASI MUSEUM DI DAERAH ISTIMEWA YOGYAKARTA - prabowo, eko tresno; Sholeh, Muhammad; Iswahyudi, Catur (Jurnal Script, 2013)
Museum is one of many attraction.destination at Yogyakarta. The presence of Geographic Information Systems would be very helpful to show complete information, and become tool to searching route of museum location to arrive there using route of Trans Jogja as used vehicles.The system is built using a web-based programming using the CodeIgniter framework, with a MySQL database. Maps feature in this study using the Google Map API. Google also supports for the manufacture of Trans Jogja path which will be integrated with the location of the museum.This Geographic Information System has a feature to search the museum, museum location search, search route to the museum using Trans Jogja, in this system there are also articles or news related to the existing museum. Using Geographic Information Systems museum is expected to be petrified visitors in search of a variety of information museums in District of Yogyakarta.Keyword : GIS, Museum, Route, Trans Jogja, Google Map.